A cooled city? Comparing human activity changes on the impact of urban thermal environment before and after city-wide lockdown. (15th May 2021) - Cai, Zhi; Tang, Yan; Zhan, Qingming
Abstract: The outbreak of the COVID-19 epidemic in early 2020 reduced human outdoor activities and changed the spatial-temporal distribution of the population. To find its changes on the impact of urban thermal environment, we applied Pearson correlation analysis and OLS linear regression model from the perspective of urban land use and the local climate zone (LCZ) scheme, and selected Wuhan City in China as a case study. The results showed that the population size decreased in most urban land use and LCZ classes due to the Spring Festival and epidemic effects, which caused residents to leave Wuhan City. As a result, the normalized surface urban heat island changes (SUHInc ) decreased by 9.41% at the city level, and a larger SUHInc occurred in commercial and industrial land. Among the LCZ classes, the built-up classes also tended to have a larger SUHInc than the natural land cover classes. However, the population size and human outdoor activity changes did not modify the spatial distribution of the urban thermal environment, because the same trends were observed for various urban land use and LCZ classes, which illustrated that the contribution of anthropogenic heat discharge on the urban thermal environment is relatively weaker. The above findings imply that it is necessary to apply different methods for various urban land uses and alleviate urban heat island. Graphical abstract: Image 1 Highlights: The COVID-19 reduced human outdoor activities. The Spring Festival combined with epidemic affects, caused 30% residents to leave Wuhan city. The changes of human activities and population size affects urban thermal environment. Larger thermal changes were appeared in commercial and industrial areas, as well as built-up LCZ classes.